Mother's adaptation process during pregnancy:A systematic review - Megananda, Nadya Karlina; Beo, Yosef Andrian; Albyn, Devanda Faiqh (PT Saintek Medika Nusantara, 2022)
Pregnant women need to adjust to the conditions of their pregnancy, both adjustments to changes in physical form, adjustments to health behavior, adjustments to physical abilities (physical performance), and psychological changes during pregnancy. This article aimed to describe the mother's adaptation process during pregnancy. The systematic review method used was to review scientific articles obtained from data-based. Articles were obtained by searching using PRISMA flow diagrams in databases, namely Science Direct, EBSCO, Pubmed, Proquest, and Google Scholar with the keywords Pregnancy, Adaptation, Process, Pregnancy Woman. The inclusion criteria were articles about the mother's adaptation process during pregnancy. The exclusion criteria are systematic review or meta-analysis articles. Articles are limited from 2010 to 2020 to ensure that relevant articles are used to date. It was found that facing pregnancy, pregnant women made many adjustments from the beginning knowing that pregnant women were planning the delivery process, supporting factors for adaptation, and supporting methods in adapting pregnant women. Pregnant women need planning and supporting factors during pregnancy to adapt to pregnancy until delivery.